The Fungus Metarhizium sp. BCC 4849 Is an Effective and Safe Mycoinsecticide for the Management of Spider Mites and Other Insect Pests - Rudsamee Wasuwan; Natnapha Phosrithong; Boonhiang Promdonkoy; Duangjai Sangsrakru; Chutima Sonthirod; Sithichoke Tangphatsornruang; Somsak Likhitrattanapisal; Supawadee Ingsriswang; Chettida Srisuksam; Kewarin Klamchao; Malinee Suksangpanomrung; Thipmanee Hleepongpanich; et al. (Insects, 2021)
Five isolates of Metarhizium sp. were evaluated for their pathogenicity against the spider mite (Tetranychus truncatus Ehara) (Acari: Tetranychidae) and Metarhizium sp. BCC 4849 resulted in the highest mortality (82%) on the 5th day post-inoculation (DPI). Subsequent insect bioassay data indicated similar high virulence against five other insects: African red mites (Eutetranychus africanus Tucker) (Acari: Tetranychidae), bean aphid (Aphis craccivora Koch) (Hemiptera: Aphididae), cassava mealybug (Phenacoccus manihoti Matile-Ferrero) (Hemiptera: Pseudococcidae), sweet potato weevil (Cylas formicarius Fabricius) (Coleoptera: Brentidae), and oriental fruit fly (Bactrocera dorsalis Hendel) (Diptera: Tephritidae), at mortalities of 92–99%, on 3rd–6th DPI, and in laboratory conditions. The pathogenicity assay against E. africanus in hemp plants under greenhouse conditions indicated 85–100% insect mortality on 10th DPI using the fungus alone or in combination with synthetic acaricide. Genome sequencing of Metarhizium sp. BCC 4849 revealed the high abundance of proteins associated with zinc-, heme-, and iron-binding; oxidation-reduction; and transmembrane transport, implicating its versatile mode of interaction with the environment and adaptation to various ion homeostasis. The light and scanning electron microscopy indicated that at 24 h post inoculation (PI), adhesion and appressorial formation occurred, notably near the setae. Most infected mites had stopped moving and started dying by 48–72 h PI. Elongated hyphal bodies and oval blastospores were detected in the legs. At 96–120 h PI or longer, dense mycelia and conidial mass had colonized the interior and exterior of dead mites, primarily at the bottom than the upper part. The shelf-life study also indicated that conidial formulation combined with an oxygen-moisture absorber markedly enhanced the viability and germination after storage at 35 °C for four months. The fungus was tested as safe for humans and animals, according to our toxicological assays.